THE STRATEGY TO SUSTAIN LIVELIHOOD DURING PANDEMIC: LESSON FROM CULINARY ENTREPRENEURS IN SALATIGA - Rio Setiawan; Aldi Herindra Lasso (Universitas Airlangga, 2023)
During the COVID-19 pandemic, sustainability of tourism-related livelihood is significantly deterred. Tourism-related SMEs, including culinary businesses, struggle to find ways to survive the pandemic. Thus, strategies to cope with the crisis becomes an important issue to elaborate. This study provides an empirical case of such struggle by presenting a case of culinary business in Salatiga, Central Jawa, Indonesia. Based on qualitative approach, this research investigates strategies of the culinary entrepreneurs to cope with the COVID-19 pandemic. Data are collected through interviews, observations and document studies. Findings show that although culinary entrepreneurs currently manage to survive, they have to struggle to maintain their livelihood. As the end of the pandemic is still unpredictable, the sustainability of their livelihood remains vulnerable.